Forensic Assistance Project: Consultant Report 1999-059 Prijedor I Federation Commission on Missing Persons - Bosniak Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Komar, Debra From 20 September through 24 September 1999 the Federation Commission on Missing Persons - Bosniak Side investigated a total of 26 sites in the area surrounding the town of Prijedor and exhumed a minimum of 69 bodies. According to the Bosniak Commission, all individuals recovered during this exhumation process were killed in 1992 by Bosnian Serb soldiers and the paramililary. All were reported to be civilians by the Bosniak Commission. Place of Exhumation: Prijedor Exhumation Site: Patrija, Patrija I, Patrija II, Patrija II A, Patrija IV, Cirkini, Kotlovača, Čauševići, Blaževići, Mutnik, Grevići, Suhi Brod, Balići, Omladinska, Softići, Softići III, Softići IV, Sušići, Mujkanovići, Crkvena, Donlagići, Mahaći, Brdani, Dera-Bešići, Kamičani, Kenjari Date of Exhumation: 20-24 September 1999 Minimum Number of Exhumed Individuals: 069